MOTIVASI BELAJAR WARGA BELAJAR MENGIKUTI PROGRAM KEJAR PAKET C DI PKBM MITRA RIAU JAYA CEMERLANG PEKANBARU - Arman Bima; Sumardi '; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on the state of the factors the motivation to study the learn to attend package C di PKBM Mitra Riau Jaya Cemerlang Pekanbaru. Because of a the motivation to study was pendorongan an establishment realized to affect mannerisms people learn to attend package C di PKBM Mitra Riau Jaya Cemerlang Pekanbaru. The formulation the research is which motivation most dominant of motivation intrinsic with extrinsic motivation people learn in following package C di PKBM Mitra Riau Jaya Cemerlang Pekanbaru?. The purpose of this research is to know where have motivation most dominant among intrinsic motivation with extrinsic motivation residents learned in following package C di PKBM Mitra Riau Jaya Cemerlang Pekanbaru. The population in research has reached 57 people learn. Then the researcher determine samples from 36 people for research and 20 people to the test, with uses the technique simple random sampling. An instrument data collection the survey by 40 a statement and if the trial live 38 statement valid for made instrument in research. Through data analysis of the quantitative descriptive analysis. So, the research results show that the motivation to study residents learn package C di PKBM Mitra Riau Jaya Cemerlang Pekanbaru In good, with an average percentage of 63%. Even though the motivation internal are more dominant than motivation external. It means residents learn motivated to study because hope or ideals available.Key words: Motivation, Motivation to study the learn to attend package C.